Impact of Temozolomide on Immune Response during Malignant Glioma Chemotherapy - Sadhak Sengupta; Jaclyn Marrinan; Caroline Frishman; Prakash Sampath (Clinical and Developmental Immunology)
Malignant glioma, or glioblastoma, is the most common and lethal form of brain tumor with a median survival time of 15 months. The established therapeutic regimen includes a tripartite therapy of surgical resection followed by radiation and temozolomide (TMZ) chemotherapy, concurrently with radiation and then as an adjuvant. TMZ, a DNA alkylating agent, is the most successful antiglioma drug and has added several months to the life expectancy of malignant glioma patients. However, TMZ is also responsible for inducing lymphopenia and myelosuppression in malignant glioma patients undergoing chemotherapy. Although TMZ-induced lymphopenia has been attributed to facilitate antitumor vaccination studies by inducing passive immune response, in general lymphopenic conditions have been associated with poor immune surveillance leading to opportunistic infections in glioma patients, as well as disrupting active antiglioma immune response by depleting both T and NK cells. Deletion of O6-methylguanine-DNA-methyltransferase (MGMT) activity, a DNA repair enzyme, by temozolomide has been determined to be the cause of lymphopenia. Drug-resistant mutation of the MGMT protein has been shown to render chemoprotection against TMZ. The immune modulating role of TMZ during glioma chemotherapy and possible mechanisms to establish a strong TMZ-resistant immune response have been discussed.